Weltstadt – who creates the city? - Böttger, Matthias (2013)
Who creates the city? Who shapes its future? – Inspired by these central questions, Weltstadt – Who creates the city? connects projects by various Goethe-Institutes and their local partners. Notwithstanding different formats and approaches, they share a common interest in testing urban visions and new constellations of actors.